Feedlot diet for Americans that results from a misspecified optimization algorithm - Springmann, M; Clark, M; Willett, W (National Academy of Sciences, 2018)
White and Hall suggest that removing animals from US agriculture would create a food supply incapable of supporting the US population’s nutritional requirements and increase nutritional deficiencies compared to the current food system. However, their analysis suffers from an uncritical use of nutritional values and optimization algorithms, and a highly unrealistic and narrow scenario design.